2018
DOI: 10.7717/peerj.4914
|View full text |Cite
|
Sign up to set email alerts
|

Discovery of digestive enzymes in carnivorous plants with focus on proteases

Abstract: BackgroundCarnivorous plants have been fascinating researchers with their unique characters and bioinspired applications. These include medicinal trait of some carnivorous plants with potentials for pharmaceutical industry.MethodsThis review will cover recent progress based on current studies on digestive enzymes secreted by different genera of carnivorous plants: Drosera (sundews), Dionaea (Venus flytrap), Nepenthes (tropical pitcher plants), Sarracenia (North American pitcher plants), Cephalotus (Australian … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
29
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 42 publications
(32 citation statements)
references
References 102 publications
1
29
0
Order By: Relevance
“…pteronyssinus has the potential to reveal biochemical pathways that could be exploited in future biocontrol strategies. These “Omic” approaches have accelerated digestive enzyme discovery [15], enabling in silico prediction of biochemical activities coupled with measurement of gene or protein expression. Potent enzymes are excreted by HDM into their surroundings as a by-product of their digestive processes, therefore the presence of putative enzymes in faeces is a strong indicator of a digestive function [16].…”
Section: Introductionmentioning
confidence: 99%
“…pteronyssinus has the potential to reveal biochemical pathways that could be exploited in future biocontrol strategies. These “Omic” approaches have accelerated digestive enzyme discovery [15], enabling in silico prediction of biochemical activities coupled with measurement of gene or protein expression. Potent enzymes are excreted by HDM into their surroundings as a by-product of their digestive processes, therefore the presence of putative enzymes in faeces is a strong indicator of a digestive function [16].…”
Section: Introductionmentioning
confidence: 99%
“…Previous studies, including literature review and comparative annotation approaches, accurately identified GO terms and KEGG enzymes strictly related to the carnivory-associated functions among the sequenced carnivorous plants available in public databases [31,32]. Based on this data, we investigated our functional annotation results and observed that U. reniformis had an extensive gene repertoire of carnivory-associated and ROS-related functions (Table 4).…”
Section: Utricularia Reniformis Displays Unique Patterns Of Carnivorymentioning
confidence: 98%
“…Cysteine cathepsins are not only lysosomal peptidases, as there is clear evidence of their localization in other cellular compartments, such as the nucleus, cytoplasm and plasma membranes (Wex et al, 2003;Hsing and Rudensky, 2005;Salminen-Mankonen et al, 2007). Of particular interest are the cysteine cathepsins found in the multi-enzyme digestive complex of some insects (Vinokurov et al, 2005(Vinokurov et al, , 2006a(Vinokurov et al, ,b, 2009Semashko et al, 2014), as well as carnivorous plants (Ravee et al, 2018). Being digestive, these cathepsins not only have a higher degradomic potential than ordinary lysosomal cathepsins because of expanded substrates, but due to the structure of their natural substrates, they also exhibit specificity that is not characteristic of most known lysosomal cathepsins.…”
Section: Introductionmentioning
confidence: 99%